Dampak Fenomena Fear of Missing Out Terhadap Kebutuhan Finansial Mahasiswa Kota Palangka Raya - Lulu Erniawati; Wahyu Akbar; Karina Awalia Zahra (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to determine the impact of the FoMO phenomenon on the financial condition of university students in Palangka Raya City. Therefore, this study aims to examine the impact of the FoMO phenomenon on the financial condition of university students in Palangka Raya City. This research is a field research using a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation on students aged over 20 years. Based on the questionnaire that the researcher distributed, there were 60 respondents who filled in. Of the 60 respondents, researchers took 18 people who became subjects in this study, namely from 6 universities in Palangka Raya. The results showed that the FoMO phenomenon has a significant impact on student financial management. The dominant negative impacts include difficulty in saving, uncontrolled spending, and increased use of paylater services or going into debt to follow the latest trends. This behavior not only burdens students' financial condition, but also worsens their ability to manage their daily finances. The study also found that FoMO can motivate self-development, career opportunity creation, and creativity, provided that students are able to manage its impact wisely. Therefore, good financial literacy is key in reducing the negative impact of FoMO and achieving a balance between following trends and healthy financial management.